2011
DOI: 10.1021/jp111398r
|View full text |Cite
|
Sign up to set email alerts
|

On the Decoupling of Relaxation Modes in a Molecular Liquid Caused by Isothermal Introduction of 2 nm Structural Inhomogeneities

Abstract: To support a new interpretation of the origin of the dynamic heterogeneity observed pervasively in fragile liquids as they approach their glass transition temperatures T g , we demonstrate that the introduction of ~2 nm structural inhomogeneities into a homogeneous glassformer leads to a decoupling of diffusion from viscosity similar to that observed during the cooling of orthoterphenyl OTP below T A, where Arrhenius behavior is lost. Further, the decoupling effect grows stronger as temperature decreases (and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 75 publications
(137 reference statements)
0
17
0
Order By: Relevance
“…Moreover, in that study, η increased when POSS was added, i.e., an increase in the POSS content had the same effect on η as a decrease in T. The increase was interpreted in terms of a "blocking effect" of POSS on the flow lines of m-cresol (see the illustration in Ref. 31), when η of the mixture is already very low. Since the propylamine group of the POSS they used 31 can form hydrogen bonds with the OH group of m-cresol, the flow lines of the m-cresol molecule would not be as simply blocked by the 2 nm POSS molecule as they would be blocked by an inert, 2 nm size spherical particle.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Moreover, in that study, η increased when POSS was added, i.e., an increase in the POSS content had the same effect on η as a decrease in T. The increase was interpreted in terms of a "blocking effect" of POSS on the flow lines of m-cresol (see the illustration in Ref. 31), when η of the mixture is already very low. Since the propylamine group of the POSS they used 31 can form hydrogen bonds with the OH group of m-cresol, the flow lines of the m-cresol molecule would not be as simply blocked by the 2 nm POSS molecule as they would be blocked by an inert, 2 nm size spherical particle.…”
Section: Discussionmentioning
confidence: 81%
“…31), when η of the mixture is already very low. Since the propylamine group of the POSS they used 31 can form hydrogen bonds with the OH group of m-cresol, the flow lines of the m-cresol molecule would not be as simply blocked by the 2 nm POSS molecule as they would be blocked by an inert, 2 nm size spherical particle. In contrast, τ m in our study decreased when the POSS content was increased which shows that η did not increase, i.e., a POSS molecule did not act to block the "flow lines" of the DGEBA molecules.…”
Section: Discussionmentioning
confidence: 98%
“…123 At lower temperatures where heterogeneities are longer-lived than τ r , molecular aspects get prominence and a departure from the SED description ensues. Results obtained from experimental studies of reactive and non-reactive dynamics in ionic liquids, 52,124,125 and those from very recent measurements after isothermal introduction of ∼2 nm structural inhomogeneity in an otherwise homogeneous liquid 126 suggest that both the static and dynamic heterogeneities could contribute to the observed decoupling between solute rotation and viscosity in these melts. In the absence of LiNO 3 (f LiBr = 1.0) the extent of decoupling becomes even stronger as one finds p = 0.50 at this composition (see Fig.…”
Section: Dynamic Fluorescence Anisotropy Measurements: Heterogeneimentioning
confidence: 89%
“…The research concerning PILs has generally focused on surfactant self-assembly [26][27][28][29][30][31][32], and their physical properties [23,24,[33][34]. Due to their excellent catalytic effects and other advantages such as easy preparation, cheap cost, and low toxicity, theirs physicochemical properties have also attracted researcher's attention [35][36][37][38]. For example, recently, Nakamoto et al have reported that PILs are processing candidates as electrolyte for electrochemical storage and conversion devices [39,40].…”
Section: Introductionmentioning
confidence: 99%